Can work experience and auditor independence improve the quality of audit opinion? - Mappamiring Mappamiring (Atestasi : Jurnal Ilmiah Akuntansi, 2020)
This study aims to determine the current condition of the audit opinion at the public accounting firm in Makassar and the effect of audit experience and independence on audit opinion at the general accounting firm in Makassar. The method used is the multiple linear regression method. This research also uses validity and reality tests, T-test (partial), F test (simultaneous), correlation coefficient test (r), determination coefficient (r2). From the results of hypothesis testing, it has been proven that work experience and independence have a significant effect on audit opinion at the public accounting firm in the city of Makassar. Audit experience plays a significant role in increasing the audit opinion. The assumption is that the higher the Auditor's knowledge, the opinion's quality will also increase the statement. Independence plays a significant role in increasing audit opinion because when various interests and interventions do not influence the Auditor, the quality of the Auditor's opinion will be increasingly objective.